2015
DOI: 10.12659/msmbr.897010
|View full text |Cite
|
Sign up to set email alerts
|

Device Conformability and Morphological Assessment After TEVAR for Aortic Type B Dissection: A Single-Centre Experience with a Conformable Thoracic Stent-Graft Design

Abstract: BackgroundThe aim of this study was to analyze device conformability in TEVAR of acute and chronic (a/c) type B aortic dissections (TBAD) using the Gore Conformable Thoracic Aortic Stent-graft (CTAG).Material/MethodsFrom January 1997 to February 2014, a total of 90 out of 405 patients in our center received TEVAR for TBAD. Since November 2009, 23 patients (16 men; median age: 62 years) were treated with the CTAG. Indications were complicated aTBAD in 15 (65%) and expanding cTBAD in 8 (35%) patients. Primary en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 30 publications
0
18
2
2
Order By: Relevance
“…Proximal landing zones 2 and 3 were also found to be associated with an increased risk of the BBC. 1,2,9,19,22 One study 18 reported the BBC as a common occurrence when the endograft was deployed in an ascending aortic Dacron graft during type II hybrid arch repair.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Proximal landing zones 2 and 3 were also found to be associated with an increased risk of the BBC. 1,2,9,19,22 One study 18 reported the BBC as a common occurrence when the endograft was deployed in an ascending aortic Dacron graft during type II hybrid arch repair.…”
Section: Resultsmentioning
confidence: 99%
“…Yet, displacement forces are greater in aneurysmal aortas compared with healthy aortas (ie, nondilated aortas such as in trauma patients) in zone 3, 7 and therefore clinical outcomes may vary based on the indication for TEVAR and the choice of the proximal landing zone. Among the potential determinants of the BBC analyzed in the literature, specific anatomic risk factors are the ones most consistently reported, namely proximal landing zones 2 and 3 1,2,9,19,22 and aortic angulation. [16][17][18][19]24,25,28 Of note, these features are often associated because zones 2 and 3 in a type III arch configuration are characterized by severe angulation and tortuosity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These topics will be addressed below. 73,74 Alternatively, a transapical, transcarotid, or transaxillary approach offer deployment strategies closer to the ascending aorta when compared to the transfemoral approach. Nonetheless, each of these approaches carry distinct risks.…”
Section: Reinterventionsmentioning
confidence: 99%
“…This approach is used to position the device parallel to the outer curve in cases with an acute angled landing zone by pushing a stiff wire. 2 -4 A 260-cm Amplatz Super Stiff™ wire (Cook, Bloomington, U.S.A.) was used to advance the delivery system of the main body. The wire tip was placed just above the aortic valve beforehand.…”
Section: Case Reportmentioning
confidence: 99%